If ∫ 0 1 ( x − 1 ) x ln 1 7 2 9 ( x ) d x = ( 2 a − 1 ) ∫ 0 ∞ e x − 1 x b d x , find the sum of integers a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
consider the integral representations of ψ n ( z ) = ∫ 0 1 x − 1 ln n ( x ) x z − 1 d x , Γ ( z ) ζ ( z ) = ∫ 0 ∞ e x − 1 x z − 1 d x the lhs is ψ n ( 1 / 2 ) .at n=1729 we use legendre duplication and differentiate it continously to get the identity 2 n + 1 ψ n ( 2 z ) = ψ n ( z ) + ψ n ( z + 1 / 2 ) → ψ n ( 1 / 2 ) = ( 2 n + 1 − 1 ) ψ n ( 1 ) = ( − 1 ) n + 1 ( 2 n + 1 − 1 ) Γ ( n + 1 ) ζ ( n + 1 ) we can use the aforementioned integrals to get the result ∫ 0 1 ( x − 1 ) x ln n ( x ) d x = ( − 1 ) n + 1 ( 2 n + 1 − 1 ) ∫ 0 ∞ e x − 1 x n d x putting n=1729 we get the answer.
Problem Loading...
Note Loading...
Set Loading...
For n ∈ Z + ,
∫ 0 1 ( x − 1 ) x ln n x d x = 2 n + 1 ∫ 0 1 ( x 2 − 1 ) ln n x d x = − 2 n [ ∫ 0 1 1 − x ln n x d x + ∫ 0 1 1 + x ln n x d x ] = − 2 n [ m = 0 ∑ ∞ ∫ 0 1 x m ln n x d x + m = 0 ∑ ∞ ( − 1 ) m ∫ 0 1 x m ln n x d x ] = − 2 n [ m = 0 ∑ ∞ ( m + 1 ) n + 1 n ! ( − 1 ) n + m = 0 ∑ ∞ ( m + 1 ) n + 1 n ! ( − 1 ) m + n ] = 2 n ( − 1 ) n + 1 Γ ( n + 1 ) ζ ( n + 1 ) ( 2 − 2 − n ) = ( − 1 ) n + 1 ( 2 n + 1 − 1 ) Γ ( n + 1 ) ζ ( n + 1 ) = ( − 1 ) n + 1 ( 2 n + 1 − 1 ) ∫ 0 ∞ e x − 1 x n d x
This makes the answer 1 7 2 9 + 1 7 3 0 = 3 4 5 9 after substituting for n = 1 7 2 9